Use of heparin in patients with severe COVID-19: What is the evidence? (Research, Society and Development, 2021)
The rapid spread of coronavirus disease (COVID-19) worldwide urges the need for studies on the illness and its management. The COVID-19 infection leads to hypercoagulation due to inflammatory cytokine release and D-dimer increase in critically ill patients, resulting in pulmonary thromboembolism (PE) and venous thromboembolism (VTE) evolving to sepsis and death. The study evaluated the currently existing evidence on heparin administration in patients with severe COVID-19. An integrative literature review was done by searching for scientific studies in the PubMed, Scopus, Embase, and Web of Science databases. The analyzed studies showed that heparin use in critically ill patients could efficiently prevent thrombotic events and reduce the exacerbated inflammatory process. However, further investigation on the effect on patients is still needed. The use of heparin in critically ill COVID-19 patients has been prescribed increasingly by doctors. But its use has not yet had its outcomes well established in the literature. Therefore, deeper investigations and new research development are needed to clarify potential beneficial effects.